O poder social - Feres, Nelma de Abreu e Lima (1974)
The objective of this study was to investigate the relationship between external locus of causality and agreemet of powerful people in mesting the demands of their subordinates. Previous research undertaken in the U.S. have shown some of the conditions that lead people in power situations to meet the demands of their dependents. This study is a partial replication of Schopler and Mathews experiment (1965) the hypothesis being that when powerful people help their subordinates more when they perceive their demand as motivated by external factors than when they perceive their demand as motivated by personal choice (internal factors). Brazilian subjects were used in this replications. Two additional hypotheses were introduced under the same design: (1) the amount of help given increases when associated with low cost (Thibaut and Kelley's hypothesis, 1967); (2) the amount of help given decreases when the subordinate’s demand is previously know by the powerful person though perceived as caused by external factors. The results indicated significant differences between the means tested in all three hypotheses of the study. The level of significance was at 05 for three hypotheses. The results were discussed within the framework of exchange theory and reactance theory. On the basis of the results, the following conclusioms see, warranted: (1) power relations do not seem to be influenced by the culture in which the agents live; (2) reaction to the loss of freedom may explain the lower degree of powerful people agreement to their subordinates demands which are previcusly known.